ISOLASI SENYAWA SITOTOKSIK DARI DAUN ANDONG (Cordyline terminalis Kunth) - Bogoriani, N. W.; Rahayu Santi, Sri; Astiti Asih, I. A. R. (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation and identification one of cytotoxic fraction have been conducted from the leaves of Andong (Cordyline terminalis Kunth). The fraction having LC50 values of 41,64 ppm contains saponin. Major isolate (7.5 mg white amorphous solid) was obtained after a series of chromatographic separations (gravity column chromatography, and preparative high performance liquid chromatography). Identification of the isolate using mass spectrometry with positive electrospray showed MW of 866 as calculated from the ion peaks m/z 889[M + Na]+, and 867[M + H]+. The ion peaks at m/z 721[(M + H) - 146]+, 703[(M + H) - 164]+, 575[(M + H) - 292]+, 557[(M + H) - 310]+ , 429[(M + H) - 438]+, and 411 [(M + H) - 456]+ of its fragments indicate the presence of three sugars (two terminal sugars and one central sugar) from methylpentose moiety with MW 164 eash linked to an agyicone of MW of 428. Proton magnetic resonance spectrum of the isolate in pyridine-d5 showed characteristic proton signals for three steroid methyls (two angular methyls and one secondary methyl) at d 1.37 (s), 0.84 (s) and 1.02 (d, J = 6.6 Hz); an exomethylene group at d 4.79 ppm and 4.71 (each br s); an ethylene group at d 5.52 ppm (br d, J = 5.4 Hz); signals of the protons linked to C26 at d 4.01 and 4.44 ppm (each d, J = 12.0 Hz), and three anomeric protons at d 6.43 ppm (br s); 5.56 ppm (br s) and 4.57 ppm (d, J = 7.0 Hz). From the above data it can be indicated that the isolate resulted is spirostan steroidal saponin.
Keywords: isolation, identification, Artemia salina Leach, Cordyline terminalis Kunth, Liliaceae